The writings of John Calvin : an introductory guide - Greef, W. de (Wulfert), 1939- (Louisville : Westminster John Knox Press, 2008)
"In this expanded edition of an invaluable resource, Wulfert de Greef guides renders through Calvin's many writings. By exploring' the historical background of each of Calvin's works and providing helpful insights into individual texts themselves, de Greef has presented Calvin students and scholars with a clear and comprehensive guide to the thought of the great Genevan reformer, A biography of Calvin, which focuses on the main events and people with whom he dealt, is an added feature of this useful reference work."--BOOK JACKET.
1. Overview of Calvin's Life -- Youth and Education up to Arrival in Geneva -- First Stay in Geneva (1536-38) -- Stay in Strasbourg (1538-41) -- Again in Geneva -- The Academy of Geneva -- Calvin's Relations with Others -- Calvin's Last Days -- 2. First Publications -- The Foreword to the Antapologia of Nicolas Duchemin (1531) -- Commentary on Seneca's De dementia (1532) -- Nicolas Cop's Academic Address (1533) -- 3. Calvin and the Bible -- Bible Translation -- Calvin's Commentaries -- Calvin's Lectures (Praelectiones) -- Calvin's Sermons -- Calvin's Contributions to the Weekly Bible Studies (Congregations) -- 4. Building Up the Church -- Fundamental Issues in Congregational Nurture -- Liturgical Structure of Public Worship -- Instruction of the Youth -- Special Assistance -- Confession of Faith: The Gallican Confession (1559) -- Church Order and Visitation -- 5. Debating with Roman Catholics -- Epistolae duae (1537) -- Religious Colloquy in Lausanne (1536) -- Correspondence with Louis du Tillet (1538) -- Responsio ad Sadoletum (1539) -- Religious Colloquies in Haguenau, Wonns, and Regensburg -- Dispute against Abuses (Traiti des reliques, 1543) -- Debating with Albertus Pighius -- Debating with the Sorbonne (1544) -- The Council of Trent and the Augsburg Interim -- 6. Debating with Other Movements and Individuals -- Anabaptists -- The Libertines -- Debating about Doctrinal Issues -- Debating with a Jew -- 7. Striving for Unity and the Ensuing Debate -- Confessio fidei de eucbaristia (1537) -- Agreement with Bullinger and Zurich (Consensus Tigurinus of 1549) -- Debate with the Lutherans Westphal and Heshusius about the Consensus Tigurinus -- 8. The Institutes -- Institutes (1536) -- Institutes (1539) -- Institutes (l543 and 1545) -- Institutes (1550) -- Institutes (1559) -- 9. Miscellaneous Publications -- Calvin as Jurist -- Document about Ecclesiastical Goods (1545) -- Two Forewords by Calvin -- Congratulation to Gabriel de Saconay (1561) -- Debating with Francois Baudouin (1561-63) -- 10. Letters -- Correspondence with Lelio Sozzini -- Correspondence with Poland -- Letter to Menso Poppius -- Correspondence with the Ministers in Montbeliard -- Correspondence with England and Scotland -- Survey of Primary Sources -- Selected Bibliography of Secondary Literature -- Chronological Index of Calvin's Writings.
Translated from the Dutch.
"Originally published as Johannes Calvijn: Zijn werk en geschriften, c1989 Uitgeverij De Groot Goudriann--Kampen Uitgeversmaatschappij J.H. Kok B.V."--T.p. verso.
Includes bibliographical references (p. 208-232) and indexes.
Translated from the Dutch.
Keywords: Calvin, Jean, -- 1509-1564.